On Annihilated Points and Approximate Fixed Points of General Higher-Order Nonexpansive Mappings - Joseph Frank Gordon; Abdul Hayee Shaikh; Augustine Annan; Yarhands Dissou Arthur; Emmanuel Akweittey; Benjamin Adu Obeng (Abstract and Applied Analysis)
In this paper, we extend the results obtained by Ezearn on annihilated points for his higher-order nonexpansive mappings to the context of general higher-order nonexpansive mappings. Precisely in his thesis, Ezearn introduced the concept of annihilated points, which extends the notion of fixed points, and it is only meaningful in the context of higher-order nonexpansive mappings and gave some mild conditions when the annihilated points could exist in strictly convex Banach spaces. In the last direction, we also extend Ezearn’s result on the approximate fixed point sequence for higher-order nonexpansive mappings to general higher-order nonexpansive mappings.